2011
DOI: 10.1200/jco.2011.36.8373
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Survivorship Care Plans: Results of a Randomized, Clinical Trial of Patients With Breast Cancer

Abstract: The results do not support the hypothesis that SCPs are beneficial for improving patient-reported outcomes. Transferring follow-up to PCPs is considered an important strategy to meet the demand for scarce oncology resources. SCPs were no better than a standard discharge visit with the oncologist to facilitate transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
293
4
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(305 citation statements)
references
References 27 publications
7
293
4
1
Order By: Relevance
“…The ability to give proper feedback with respect to endocrine therapyrelated issues may be suboptimal among nonspecialists and hence decrease adherence. However, a Canadian study reported that primary health care doctors can follow-up patients with breast cancer without adversely affecting outcome (49). As per recent guideline changes in southern Sweden, patients no longer routinely follow-up with their breast cancer physician beyond the first year postsurgery.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to give proper feedback with respect to endocrine therapyrelated issues may be suboptimal among nonspecialists and hence decrease adherence. However, a Canadian study reported that primary health care doctors can follow-up patients with breast cancer without adversely affecting outcome (49). As per recent guideline changes in southern Sweden, patients no longer routinely follow-up with their breast cancer physician beyond the first year postsurgery.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the barriers are insufficient consensus about the required content of the scp and insufficient staff time to prepare and deliver the scp 43 . Grunfeld et al 49 reported that scps are not seen as any better or different from the standard discharge or transfer to the community. However, that particular clinical trial was neither a longitudinal study nor an exploration of cultural or social factors that might be important to take into consideration, especially the ways in which people experience health and illness and their expectations for health care delivery.…”
Section: Recommendations For Cancer Care Providersmentioning
confidence: 99%
“…Subsequently, the American College of Surgeons' Commission on Cancer (CoC) called for implementation of SCPs by January 2015 in all accredited programs [2]. While the practice community strives to comply with the CoC directive and impending deadline, the scientific community is scrambling to catch up: evidence regarding the impact of survivorship care plans and care planning interventions remains scant, largely developmental, and somewhat controversial, as outlined in a series of earlier commentaries and articles [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The challenges to the development of science in this area have included the absence of a conceptual framework guiding empirical efforts and a lack of consensus and recommendations about the appropriate constructs and process and outcome measures to use in assessing survivorship care planning.…”
mentioning
confidence: 99%